The Problems of Learning to Read and Write the Qur'an and its Solutions (Case Study at Madrasah Diniyah Takmiliyah Awaliyah Al-Khairiyah Winong) - Uun Kurnaesih; Tihami Tihami; Hunainah Hunainah (UIN Sunan Gunung Djati Bandung, 2021)
This study attempts to present an overview of the problems and their proposed solutions in learning to read and write the Qur'an at Madrasah Diniyah Takmiliyah Awaliyah in Winong Village, Mancak District, Serang Regency, Banten Province. Respondents of this study were students of class v, amounting to 16 people.This research uses descriptive qualitative method by collecting data from observations, interviews and documentation. The results of this study are expected to be able to find obstacles or problems in BTQ learning and provide solutions in overcoming the problems of learning to read and write the Qur'an at the Madrasa.The problems are students' laziness to learn to read and write, difficulty in pronouncing letters according to their Makhraj, so students find it difficult to learn tajwid and use it in reading the Qur'an, and the method of habituation in BTQ learning at the madrasa has not been applied.The solution that can be offered is that parents and teachers continue to strive to provide motivation to learn to read and write with fun methods, choose the right method in learning the hijaiyah letters, and motivate students to learn tajwid in an appropriate and fun method, and the need to apply the habituation method in BTQ learning at the Madrasah.